Rv1258c acts as a drug efflux pump and growth controlling factor in Mycobacterium tuberculosis. (March 2022) - Jia, Hongbing; Chu, Hongqian; Dai, Guangming; Cao, Tingming; Sun, Zhaogang
Abstract: The possible role of efflux pump as a survival mechanism in Mycobacterium tuberculosis ( M. tb ) is gaining an increasing attention. Previously, Rv1258c (Tap) and its certain mutations confer the clinically relevant drug resistance. In this study, we found new mutations of Rv1258c in G195C, T297P and I328T. Effect of modulating T297P and I328T on the drug resistance by knockout and complement in M. tb H37Rv showed that M. tb ΔRv1258c showed a slightly lower MIC for rifampin, ethambutol, ofloxacin, amikacin, capreomycin and streptomycin than M. tb H37Rv WT and the complement. Rv1258c T297P and Rv1258c I328T showed an increased drug resistance to ethambutol and capreomycin than the complement of Rv1258c WT. Most importantly, M. tb ΔRv1258c exhibited a slow growth in the normal culture medium. TMT-based quantitative proteomics analysis of M. tb ΔRv1258c and WT showed that the knockout of Rv1258c greatly down-regulated the expression of the ribosome system and one of the special five type VII secretion systems, ESX-3, which impaired the bacterial growth. These results indicate that the newly found T297P and I328T mutations of Rv1258c contributed to an increased resistance to ethambutol and capreomycin, and Rv1258c as growth controlling factor influencing the growth of M. tb. Research highlights: Efflux protein encoded by Rv1258c, as a survival mechanism, is mediated resistance in Mycobacterium tuberculosis ( M. tb ). Newly found T297P and I328T mutation of Rv1258c contribute to more resistant to ethambutol and capreomycin. And Rv1258c as growth controlling factor influences the growth of M. tb.